Thermo-optically induced transparency on a photonic chip - Marco Clementi (Nature Publishing Group, 2021)
Thermo-optically induced transparency is a versatile implementation of EIT-analogs in an integrated photonic platform, at arbitrary wavelength of interest, room temperature and in a practical, low cost, and scalable system.